2008
DOI: 10.1007/bf03076412
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive neuropsychological approach to false memory: Korsakoff patients and the DRM paradigm

Abstract: Although false memories have been studied extensively within the field of cognitive psychology, the role of cognitive neuropsychology in false memory research has been rather limited. Therefore, the present article aims at giving an integrated overview of both the neuropsychological study of amnesia and research on false memories. After considering some of the most important predecessors in the study of memory distortions/illusions, a listlearning paradigm designed to elicit and investigate false memories is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 114 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…In the last few decades, researchers have inclined towards using more advanced tools to study consumers' purchasing behavior and their memory formation while receiving advertisements for different brand products (Lucchiari & Pravettoni, 2012;Camarrone & Van Hulle, 2019). For instance, in the pseudo-memory research, it was shown that the prefrontal cortex and hippocampus reported in previous studies are involved in false memory formation (Schacter, 1996;Van Damme & d'Ydewalle, 2009). It has been reported that activations of some brain areas including frontal-parietal parts, left hippocampus, and bilateral middle temporal gyrus might be different for true and false memories (Dennis et al, 2008).…”
Section: Use Of Neuroimaging Techniques To Investigate the Neural Mec...mentioning
confidence: 99%
“…In the last few decades, researchers have inclined towards using more advanced tools to study consumers' purchasing behavior and their memory formation while receiving advertisements for different brand products (Lucchiari & Pravettoni, 2012;Camarrone & Van Hulle, 2019). For instance, in the pseudo-memory research, it was shown that the prefrontal cortex and hippocampus reported in previous studies are involved in false memory formation (Schacter, 1996;Van Damme & d'Ydewalle, 2009). It has been reported that activations of some brain areas including frontal-parietal parts, left hippocampus, and bilateral middle temporal gyrus might be different for true and false memories (Dennis et al, 2008).…”
Section: Use Of Neuroimaging Techniques To Investigate the Neural Mec...mentioning
confidence: 99%